The Effects of Democratic Leadership Style, Intrinsic Motivation, and the Organizational Environment on Employee Job Satisfaction at Elmas Fresh - Aditya; Hadi, Syamsul; Ratna Purnamarini, Tri (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to investigate the effects of democratic leadership style, intrinsic motivation, and organizational environment on employee job satisfaction at Elmas Fresh Company. The approach used in this study was a quantitative method. Data were collected by distributing questionnaires to all employees of Elmas Fresh, employing a sampling technique. The data obtained online were subsequently analysed using multiple linear regression with the aid of SPSS software. The research results indicate that democratic leadership style and intrinsic motivation have a positive and significant effect on employee job satisfaction. Partially, the organizational environment does not have a significant effect; although the direction of its influence is positive, statistically, its impact is not strong enough. Simultaneously, democratic leadership style, intrinsic motivation, and organizational environment together have a significant influence on employee job satisfaction at Elmas Fresh Company. It is recommended that the company provide appreciation, maintain employees’ intrinsic motivation, and pay attention to aspects of supporting employee competence development so that employee job satisfaction remains maintained and improves.